Correlation of Anthropometric and Lipid Markers in GMC Jammu Medical Students (Indian Journal of Public Health Research & Development, 2023)
Background: The prevalence of cardiovascular diseases are likely to rise as a result of lifestyle-related risk factors.Due to their hectic schedules and lack of time for extracurricular activities, medical students were chosen for thestudy because they are more likely than other populations to develop lifestyle illnesses.Objectives: To explore the connection of anthropometric and biochemical lipid profile markers to assess obesityrisk in medical students.Materials and methods: 180 MBBS students from Government Medical College, Jammu, participated in the study.The body mass index (BMI) was calculated using anthropometric measurements of body weight (BW), bodyheight (BH), together with waist circumference (WC), and hip circumference (HC), as well as the waist-to-hip ratio(W/H ratio). Using blood samples, a lipid profile was calculated.Results: According to the survey, 16.11% of Group 2 students were overweight, and 3.89 % were obese. Group 1consisted of 80% normal subjects. Between two BMI groups and Lipid profile, a statistically significant differencewas discovered. There was a negative correlation between Waist circumference and HDL cholesterol. The BMIwas negatively correlated with HDL-cholesterol and positively correlated with triglyceride.Conclusion: The prevalence of cardiovascular risk factors such as obesity, hypertension, and elevated triglyceridesis high among medical students. Therefore, it may be deduced that healthy lifestyles should be adopted at a youngage because medical students are the future medical professionals.
Keywords: Anthropometric measures, Lipid profile, Medical students, Obesity.